Editorial - Zainan Nazri, Nurul Jannah (IIUM Press, 2024)
The February issue of Al-Burhan journal commences with an illuminating exploration into the profound realm of Maqāṣid al-Qur’ān. This meticulous analysis unveils the inherent noble goals of preservation, justice, compassion, and knowledge within the Quranic framework. By adeptly integrating expert insights and diverse methodologies, the study not only sheds light on the nuanced understanding of Maqāṣid but also accentuates its enduring relevance across varied contexts and epochs. It eloquently advocates for a just and compassionate way of life rooted in Islamic principles, fostering harmony among diverse communities, while poignantly emphasising the Qur’ān’s profound significance as a timeless source of divine wisdom.